Dynamics of structures: theory and applications to earthquake engineering - Chopra, Anil K (Pearson, 2007)
Dynamics of structures: theory and applications to earthquake engineering / Chopra, Anil K. -- New Delhi: Pearson, 2007 624.1762 C549e3 3rd ed No. of Copies : 1